2019
DOI: 10.1021/acsapm.9b00771
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Chitosan-g-Polyisobutylene Graft Copolymers: Synthesis, Characterization, and Properties

Abstract: The amphiphilic acylated chitosan-g-polyisobutylene copolymers (ACS-g-PIB) could be achieved via highly effective nucleophilic substitution of living PIB chains carrying the oxonium ion (PIB-THF n +) with −NH2 side groups along the ACS backbone, in which the grafting number (G N) was mediated by changing [PIB-THF n +]/[−NH2]. The obvious microphase separation micromorphology formed in copolymers due to incompatibility between the hydrophilic backbone and hydrophobic branches. Crystallization from the ACS bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…3d) have rough surfaces with holes and particles. This may be because the introduction of organic structures leads to the destruction of the hydrogen bonds between chitosan, and further leads to micro-phase separation, 43 the weak intermolecular force, and the change of the morphology.…”
Section: Resultsmentioning
confidence: 99%
“…3d) have rough surfaces with holes and particles. This may be because the introduction of organic structures leads to the destruction of the hydrogen bonds between chitosan, and further leads to micro-phase separation, 43 the weak intermolecular force, and the change of the morphology.…”
Section: Resultsmentioning
confidence: 99%
“…10 In general, antioxidants, notably cysteine (Cys), glutathione (GSH), and ascorbic acid (AA) maintain the redox homeostasis of cells and tissues. 13 However, because of the wide range of antioxidants and their probable interactions, the analysis of individual antioxidants is challenging. Therefore, the total antioxidant capacity (TAC) is used to measure antioxidant activity 14 and describes the number of free radicals that a test solution can scavenge from samples of various natural origins.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was observed that the LCST of the copolymer synthesized using PNVCL was enhanced near physiological conditions, which is useful in drug delivery applications. ,, Out of the different techniques, graft copolymerization can be more facile to obtain desired properties from different parts of the polymer (backbone and branches). In this respect, the synthesis of graft copolymers with different polymeric chains became more useful in targeted drug delivery. …”
Section: Introductionmentioning
confidence: 99%